Struthanthus martianus, a replacement name for the illegitimate Struthanthus vulgaris Mart. ex Eichler (Loranthaceae) - Dettke, Greta Aline; Waechter, Jorge Luiz (Phytotaxa, 2012)
Struthanthus martianus Dettke & Waechter is proposed as a replacement name for the illegitimate name Struthanthus vulgaris Mart. ex Eichler, a later homonym of Struthanthus vulgaris (Vell.) Mart. (= Struthanthus marginatus (Desr.) Blume). A neotype for Loranthus vulgaris Vell. is also designated.